Prevalence and risk factors of tobacco abuse in Rishikesh - Kumar, Deeapk; Kishore, Surekha; Khapre, Meenakshi; Singh, Mahendra; Jain, Bhavna; Bhadoria, Ajeet Singh (Indian Journal of Community Health, 2020)
Introduction: Tobacco is the most common form of substance abuse. Commonest evil of modern society is use of tobacco, though alcohol is equally harmful as tobacco but the accessibility of tobacco and its product are far easier for any individua. Aim & Objective: To determine the prevalence of tobacco abuse in the community and its association with sociodemographic factors of study participants. Materia & Methods: A community based cross-sectional study was conducted among 804 study participants of age group 15 – 60 years in Rishikesh, Uttarakhand. Since the population of urban and rural area is almost equal, so to get equal representative 402 study participants were selected from each area. Data was collected in MS Excel and analyzed using SPSS version 23 using appropriate statistical techniques like percentage, chi-square test and p-value. Results: Overall prevalence of substance abuse was found to be 37.4% out of which the prevalence of current users was 31.34%. Conclusion: Present study revealed that in spite of having strict law for prohibition of substance abuse, people are still addicted. There is a need to change either in law or in behavior of people at large.